Development of a Colloidal Gold-Based Immunochromatographic Strip Targeting the Nucleoprotein for Rapid Detection of Canine Distemper Virus - Zichen Zhang; Zhuangli Bi; Qingqing Du; Miao Zhang; Linying Cai; Yiming Fan; Jingjie Tang; Mingxing Hu; Shiqiang Zhu; Aoxing Tang; Guijun Wang; Guangqing Liu; et al. (Biosensors)
Canine distemper, a fatal and highly transmissible disease caused by the canine distemper virus (CDV), poses a major threat to the companion animal industry. An urgent need exists for a rapid, specific, and simple method for the detection of this disease in order to improve its prevention and control. In this research, two monoclonal antibodies (mAbs), 1D3E9 and 1H9B7, were prepared, both of which specifically recognize the nucleoprotein (N protein) of CDV, and an immunochromatographic assay for CDV detection was subsequently developed using these mAbs. The results showed that both mAbs belong to the IgG1 subclass with kappa light chains. 1D3E9 was found to recognize the linear epitope 410AGPKQSQITFLH421, while 1H9B7 targeted the epitope 450HFNDERFPGH459. The test strips exhibited high specificity and good stability for up to two months when stored at 4, 25, and 37 °C. The assay exhibited a sensitivity of 102.39 TCID50/0.1 mL. When compared with RT-PCR for detecting CDV in clinical samples, the concordance rate was 91.67%. Thus, this method shows great potential for facilitating rapid on-site detection of CDV and could be highly beneficial from the viewpoint of disease surveillance and control.